Real-world experience of how chlorhexidine bathing affects the acquisition and incidence of vancomycin-resistant enterococci (VRE) in a medical intensive care unit with VRE endemicity: a prospective interrupted time-series study - Jin Woong Suh (BMC, 2021)
Abstract Background Critically ill patients in intensive care units (ICUs) often acquire opportunistic infections or are colonized by vancomycin-resistant enterococci (VRE), which limits therapeutic options and results in high case-fatality rates. In clinical practice, the beneficial effects of universal chlorhexidine gluconate (CHG) bathing on the control of VRE remain unclear. This study aimed to investigate whether 2% CHG daily bathing reduced the acquisition of VRE in the setting of a medical ICU (MICU) with VRE endemicity. Methods This quasi-experimental intervention study was conducted in a 23-bed MICU of a tertiary care hospital in Korea from September 2016 to December 2017. In a prospective, interrupted time-series analysis (ITS) with a 6-month CHG bathing intervention, we compared the acquisition and incidence of VRE and the incidence of methicillin-resistant Staphylococcus aureus (MRSA) and carbapenem-resistant Acinetobacter baumannii (CRAB) between the pre-intervention and intervention periods. The primary and secondary outcomes were a change in the acquisition of VRE and incidence of VRE, MRSA, or CRAB between the two periods, respectively. Results All the adult patients admitted to the MICU were enrolled in the pre-intervention (n = 259) and intervention (n = 242). The overall CHG daily bathing compliance rate was 72.5%. In the ITS, there was a significant intervention effect with a 58% decrease in VRE acquisition (95% CI 7.1–82.1%, p = 0.038) following the intervention. However, there was no significant intervention effects on the incidence trend of VRE, MRSA, and CRAB determined by clinical culture between the pre-intervention and intervention periods. Conclusion In this real-world study, we concluded that daily bathing with CHG may be an effective measure to reduce VRE cross-transmission among patients in MICU with a high VRE endemicity.